Unexpected Lung Metastasis After Left Hemithyroidectomy for Follicular Adenoma in a Young Adult Male: A Case Report - Akhter, Papia; Ferdous, Jasmine; Jabin, Zeenat; Begum, Fatima (Bangladesh Journal of Nuclear Medicine, 2021)
Follicular neoplasms of the thyroid gland are benign follicular adenoma and follicular carcinoma. To distinguish follicular carcinoma from a follicular adenoma based on cytologic, sonographic or clinical features alone is very difficult. As follicular adenoma of the thyroid is a benign tumor usually do not metastasize. Here, a case is presented with follicular variant of papillary thyroid carcinoma (FVPTC) with lung metastasis which was treated as follicular adenoma four years back. Patient had left hemithyroidectomy for follicular adenoma and ignored to have regular follow up. He suddenly developed fever, chest pain and dry cough. CT scan evaluated a fairly big lung mass which eventually came out as metastatic follicular carcinoma. From this reported case, it is evident that regular checkup of patient with follicular adenoma should be ensured for early diagnosis of further transformation of adenoma to malignancy. Bangladesh J. Nuclear Med. 22(2): 157-160, Jul 2019